Interpreting Straw Man Argumentation : The Pragmatics of Quotation and Reporting - Macagno, Fabrizio; Walton, Douglas (Springer International Publishing : Imprint: Springer, 2017)
This book shows how research in linguistic pragmatics, philosophy of language, and rhetoric can be connected through argumentation to analyze a recognizably common strategy used in political and everyday conversation, namely the distortion of another's words in an argumentative exchange. Straw man argumentation refers to the modification of a position by misquoting, misreporting or wrenching the original speaker's statements from their context in order to attack them more easily or more effectively. Through 63 examples taken from different contexts (including political and forensic discourses and dialogs) and 20 legal cases, the book analyzes the explicit and implicit types of straw man, shows how to assess the correctness of a quote or a report, and illustrates the arguments that can be used for supporting an interpretation and defending against a distortion. The tools of argumentation theory, a discipline aimed at investigating the uses of arguments by combining insights from pragmatics, logic, and communication, are applied to provide an original account of interpretation and reporting, and to describe and illustrate tactics and procedures that can be used and implemented for practical purposes.. This book will appeal to scholars in the fields of political communication, communication in general, argumentation theory, rhetoric and pragmatics, as well as to people working in public speech, speech writing, and discourse analysis.
Keywords: Linguistics.; Political communication.; Pragmatics.; Political sociology.; elektronické knihy; electronic books